2019
DOI: 10.21276/ijcmr.2019.6.11.42
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABO Blood Group Phenotype and Reaction to Academic Stress in Young Medical Students

Abstract: Introduction: Professional medical education needs hard work, good physical and mental health. In previous studies there is no scientific consensus that a relationship exists between the ABO blood group and personality traits. In this current study we tried to find out association between different blood groups and different type of stressors like physical, environmental, interpersonal and academic in young medical students. Material and methods: This Descriptive Cross sectional study was conducted at Rashid L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study done to assess the association between blood groups and various stressors like physical, environmental, interpersonal and academics in medical students revealed that all variables stressors had insignificant relationships with blood group [75].…”
Section: Association With Psychiatric Disordersmentioning
confidence: 99%
“…A study done to assess the association between blood groups and various stressors like physical, environmental, interpersonal and academics in medical students revealed that all variables stressors had insignificant relationships with blood group [75].…”
Section: Association With Psychiatric Disordersmentioning
confidence: 99%